ARTIFICIAL SHADE ADAPTATION AND POPULATION DENSITY ON SWISS CHARD (Beta vulgaris subsp. Cicla (L) W.D.J Koch) IN URBAN AR-EA - Rofiqoh Ria; Benyamin Lakitan; Firdaus Sulaiman; Yakup Yakup; Zaidan P Negara; Susilawati Susilawati (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Swiss chard is a leafy vegetable that is high in nutrients, vitamins, minerals, protein, and antioxidants that are beneficial to human health. Swiss chard. Swiss chard is generally cultivated in the Mediterranean climate, grows well in full sunlight, air temperatures 14-21oC, and can still survive at temperatures close to light frost. The aim of this study to evaluate efficient plant densi-ties in urban limited land area and looking at the response of Swiss chard plant to reduc-ing the intensity of sunligt of 45%, 55% and 80%.in urban tropic area. This research was used 4 different artificial shading i.e 0% (control, shade 45%, shade 55% and shade 80%. Microclimate was measured per each shade for 14 days i.e., air temperatur, soil temperature, air humidity, and soil moisture using a data logger meter. Shade with intensity 80% is proven to reduce air temperate and soil temperature, but also inhibits the growth and development of Swiss chard plants. Population 1plant/pot gives the best growth and yield of Swiss chard per plant, 3 plants/pot increased total fresh weight per cultivation area, thereby maximize the use of limited urban land